“Doing good and feeling good” Relationship between authentic leadership with followers' work engagement: The mediating role of hedonic and eudaimonic wellbeing - Farid, Tahir; Iqbal, Sadaf; Basahal, Abdulrahman S.; Khattak, Amira; Khan, Muhammad Khalil; Salam, Mohammad Asif (Frontiers in Public Health, 2022)
Abstract Authentic leadership appeared as a positive leadership behavioral style that has attracted academicians and practitioners' attention by focusing on a healthy workplace environment and its influence on followers' valued workplace relationship outcomes such as employees' work engagement. From the lens of social exchange perspective, the researchers have tested a unified model of authentic leadership and proposed that authentic leaders influence followers’ well-being (hedonic well-being and eudaimonic well-being) and work engagement. In addition, the researcher examined the mediating role of hedonic well-being and eudaimonic well-being. By using a time-lagged design, the data were collected from 250 telecom sector workers employed in the capital city Islamabad, Pakistan. We found the positive influence of authentic leadership on followers' work engagement and on employees' hedonic and eudaimonic well-being. The results also indicated the positive mediating effect of hedonic well-being and eudaimonic well-being on the relationship between authentic leadership on followers' work engagement. The theoretical and practical implications of the study were discussed